The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1021/acsami.8b02678
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable Thin-Film Transistors Based on Indium Oxynitride Semiconductor

Abstract: In this study, the properties of indium oxynitride (InON) semiconductor films grown by reactive radio frequency sputtering were examined both experimentally and theoretically. Also, thin-film transistors (TFTs) incorporating InON as the active layer were evaluated for the first time. It is found that InON films exhibit high stability upon prolonged exposure to air and the corresponding TFTs are more stable when subjected to negative bias illumination stress, compared to devices based on indium oxide (InO) or z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…We have also investigated a hybrid nanoconstruct consisting of pPBA, aptamer, and AuNPs to endow high antioxidative activity ( Figure ). [ 176 ] AuNPs were first decorated with a hybrid DNA strand that has a connected sequence of TNF‐α aptamer and ATP aptamer. ATP was attached with ATP aptamer as secondary “bridges” and subsequently, the AuNPs were coated with pPBA by forming phenylboronic ester between PBA and diols of ATP.…”
Section: Polymer‐based Delivery Of Antioxidantsmentioning
confidence: 99%
“…We have also investigated a hybrid nanoconstruct consisting of pPBA, aptamer, and AuNPs to endow high antioxidative activity ( Figure ). [ 176 ] AuNPs were first decorated with a hybrid DNA strand that has a connected sequence of TNF‐α aptamer and ATP aptamer. ATP was attached with ATP aptamer as secondary “bridges” and subsequently, the AuNPs were coated with pPBA by forming phenylboronic ester between PBA and diols of ATP.…”
Section: Polymer‐based Delivery Of Antioxidantsmentioning
confidence: 99%
“…Several studies have reported a reduction of the PPC while reacting with the visible or near-infrared light of organic/inorganic or low-dimensional material/inorganic hybrid structure devices. , With regard to material or structural approaches, some studies considered the applied gate bias pulse sequence, which can rapidly recombine generated electron–hole pairs or trapped carriers upon light exposure. , However, these methods come with their own challenges, including difficulty controlling the process conditions, the unintended interface with the ex situ process, and the need for an additional circuit and metal line for the gate pulse bias. It has also been reported that metal oxynitride complexes, such as zinc oxynitride (ZnON) or indium oxynitride (InON), with multianions of oxygen and nitrogen have a low PPC effect because the high p orbital (N 3– ) compared to the oxygen 2p orbital can reduce the number of oxygen vacancies by screening the V o states. These metal oxynitride semiconductor-based TFTs have gained attention as next-generation photoelectronics device due to their not only optical properties such as a smaller band gap, which can absorb the visible–near-infrared region light, but also the high electrical characteristics compared to conventional metal oxide semiconductor-based one. On the other hand, it is known that ZnON thin films are relatively unstable under high-humidity conditions compared to other conventional oxides as ZnON could change to ZnO after a certain period, and ZnON-based TFTs also suffer from the PPC phenomenon caused by trapped photogenerated holes at the interface with the gate insulator or by defect states.…”
Section: Introductionmentioning
confidence: 99%
“…There has been extensive research on thin-film transistors (TFTs) because they are integral components of most electronic devices. In general, TFTs are fabricated with a Si-type semiconductor (e.g., a-Si:H and LTPS) and an inorganic gate-insulating layer. , New demands placed on TFT devices have led to the development of new types of semiconductors because Si-based TFTs have several limitations, including low mobility (a-Si:H), high process costs (LTPS), poor large-area uniformity (LTPS), and high leakage current (a-Si:H, LTPS). Among the various types of semiconductors other than silicon, amorphous oxide semiconductors, particularly amorphous In-Ga-Zn-O (a-IGZO), have been commercialized because of their advantages over Si-based semiconductors, including room-temperature fabrication and high mobility above 10 cm 2 /(V s), even in amorphous structures. , Such a-IGZO TFTs are generally fabricated with an inorganic insulating layer such as SiN x or SiO x .…”
Section: Introductionmentioning
confidence: 99%